The Sensitizing Mystery Of Taxanes- A Review - Pinto, Melisha Rolita; Santhosh, Athul (Journal of Orofacial Research, 2017)
Synchronized use of radiotherapy and chemotherapy has been the gold standard in the treatment of resectable as well as locally advanced head and neck cancer over the past few decades. Radiosensitizers play a key role in sensitizing the tumor cells to radiation, thereby surpassing the normal cells from radiation, thus protecting them. Among the many available radiosensitizers, taxanes being hydrophobic mitotic inhibitors, have indisputably proven effective in the treatment of many malignancies. This review focuses on taxane as a potential radiosensitizer in the treatment of head and neck squamous cell carcinomas.